Wasp Parasitoid, Diadegma insulare (Cresson) (Insecta" Hymenotera: Idhneumonidae) - Andrei Sourakov; Everett Mitchell (EDIS)
This document is EENY-124 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2000.